1970
DOI: 10.3329/bjvm.v6i2.2334
|View full text |Cite
|
Sign up to set email alerts
|

Sero-surveillance and immunization in sheep and goats against peste des petits ruminants in Bangladesh

Abstract: The sero-surveillance and immunization studies on Peste des Petits Ruminants (PPR) in non-descriptive indigenous sheep and Black Bengal goats aged between 5 to 12 months were carried out in the district of Mymensingh during the period from June to November 2003. Sero-prevalence of PPR by using competitive enzyme linked immunosorbent assay (C-ELISA) was conducted on 100 sheep and 100 goats which were selected randomly from 10 different areas in the district of Mymensingh. Of the 100 sheep and 100 goats tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 7 publications
3
17
2
1
Order By: Relevance
“…In the present study, the disease differed significantly ( P<0.05) between vaccinated and non vaccinated goats, suggesting that non vaccinated animals are at a higher risk to PPR. Vaccination against PPR leads to decrease in the disease prevalence but cannot protect absolutely [16]. This efficacy of PPR vaccine in reducing the prevalence of PPR was also reported [17].…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, the disease differed significantly ( P<0.05) between vaccinated and non vaccinated goats, suggesting that non vaccinated animals are at a higher risk to PPR. Vaccination against PPR leads to decrease in the disease prevalence but cannot protect absolutely [16]. This efficacy of PPR vaccine in reducing the prevalence of PPR was also reported [17].…”
Section: Discussionmentioning
confidence: 96%
“…57,59,62,65,66,67,68,70,72,74,79,80,81,84,86,87,88,89,90,93,94,95,97,98,99,105,106,109,112,113,114,116,117,118,119,120,121,125,126,128,130,131,132,133,135,137,138,139,141,142,145,147,…”
Section: Study Eligibility Form: Performance Of Diagnostic Tests For mentioning
confidence: 99%
“…The overall seroprevalence of PPR was 26.03% in selected areas in Bangladesh. Whereas Razzaque et al, 2004 andBanik et al, 2008 who found the seroprevalence of PPR is 36% in goat and BLRI, 2008 were found the seroprevalence of PPR is 33.34% in sheep. The main cause of this low seroprevalence evidence showed that those were well non organized farm and no history of vaccination.…”
Section: Resultsmentioning
confidence: 99%